Diseño e Implementación de redes IPv6 en MIPYMES: caso laboratorio de informática (2013)
This degree project was carried out in order to design and simulate an implementation of IPv6 networks in the computer laboratories of the Colombian School of Engineering Julio Garavito whose infrastructure is similar to that of a MiPyme, for this reason it is important to clarify that it is also it wanted to observe if the IPv4 network currently used and the IPv6 are or could be compatible and generate traffic between them.